Augmented Reality Media Versus Molymod Media: Comparative Study on Students Spatial Ability in Chemical Bonding - Yenni Kurniawati; Handayani Wulandari; Faruku Aliyu (Universitas Syiah Kuala, 2025)
Spatial ability is a fundamental cognitive skill in chemistry education, particularly in facilitating the visualization of abstract molecular structures, geometric shapes, and spatial relationships among atoms. This research aimed at comparing the uses of augmented reality (AR) media and molymod demonstration media in supporting student spatial ability on chemical bond lesson at the tenth grade of Islamic Integrated Senior High School of Al-Fityah Pekanbaru. Comparative method was used with quantitative approach and pretest-posttest group design in the experimental group I use AR media and the experimental group II use molymod media. Measuring spatial ability was carried out through spatial ability test questions including spatial ability indicators. The research findings showed that the score of significance (2-tailed) was 0.016 lower than 0.05, so there was a significant difference between the experimental groups. In addition, the mean percentage of N-gain score of spatial ability in the AR group was 44% which was in less effective category, and the score of the molymod group was 59.94% which was in quite effective category